2013
DOI: 10.1111/nure.12017
|View full text |Cite
|
Sign up to set email alerts
|

Dairy and blood pressure: a fresh look at the evidence

Abstract: The Dietary Guidelines for Americans, 2010 indicated there is moderate evidence for an association between the consumption of dairy foods and lower blood pressure in adults; however, it also stated that more evidence was needed, especially in clinical trials, to fully delineate a causal relationship. The purpose of this review is to provide background by examining the historical literature and the evidence reviewed by the 2010 Dietary Guidelines Advisory Committee, to examine the gaps in knowledge indicated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 59 publications
1
31
0
1
Order By: Relevance
“…A systematic review of the literature, published in 2011, concluded that the evidence from 19 prospective cohort studies was suggestive of a protective effect of dairy consumption on the risk of overweight and obesity . Most recently, a prospective study of more than 33,000 women in Sweden found an inverse association between total dairy food intake and risk of myocardial infarction, and a recent review concluded that the preponderance of evidence indicates dairy foods are beneficially associated with lower blood pressure . Another recent meta‐analysis of seven cohort studies showed the overall positive role of dairy consumption on the risk of T2D, and a subgroup analysis suggested that milk and yogurt consumption were most strongly associated with overall risk reduction compared to high‐fat dairy .…”
Section: Role Of Dairy In the Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of the literature, published in 2011, concluded that the evidence from 19 prospective cohort studies was suggestive of a protective effect of dairy consumption on the risk of overweight and obesity . Most recently, a prospective study of more than 33,000 women in Sweden found an inverse association between total dairy food intake and risk of myocardial infarction, and a recent review concluded that the preponderance of evidence indicates dairy foods are beneficially associated with lower blood pressure . Another recent meta‐analysis of seven cohort studies showed the overall positive role of dairy consumption on the risk of T2D, and a subgroup analysis suggested that milk and yogurt consumption were most strongly associated with overall risk reduction compared to high‐fat dairy .…”
Section: Role Of Dairy In the Dietmentioning
confidence: 99%
“…50 Most recently, a prospective study of more than 33,000 women in Sweden found an inverse association between total dairy food intake and risk of myocardial infarction, 51 and a recent review concluded that the preponderance of evidence indicates dairy foods are beneficially associated with lower blood pressure. 52 Another recent meta-analysis of seven cohort studies showed the overall positive role of dairy consumption on the risk of T2D, and a subgroup analysis suggested that milk and yogurt consumption were most strongly associated with overall risk reduction compared to high-fat dairy. 53 In contrast, low-level dairy consumption, for example in the case of self-perceived lactose intolerance, results in lower intakes of calcium and other nutrients and is associated with hypertension and diabetes in adults.…”
Section: Role Of Dairy In the Dietmentioning
confidence: 99%
“…Excluded from the review were studies that pertained to dairy consumption and known risk factors for CVD, such as elevated blood lipids, hypertension, and type 2 diabetes. Recent reviews on the subject of dairy/dairy components and their relationship with cardiometabolic health [8], blood pressure [9], and type 2 diabetes [10] are available for reference.…”
Section: Introductionmentioning
confidence: 99%
“…bulgaricus, characterized by a smooth, viscous gel with delicate walnutty flavor [1][2][3]. It is especially popular in Europe, North America and the Middle East.…”
Section: Introductionmentioning
confidence: 99%